2016
DOI: 10.1080/00028487.2016.1235612
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of River Herring Spawning Runs in a Chesapeake Bay Coastal Plain Stream using Imaging Sonar

Abstract: Recent declines in anadromous river herring (Alewife Alosa pseudoharengus and Blueback Herring A. aestivalis) have been documented in much of their range using fishery-independent spawning run counts. A lack of rigorous long-term run counts and demographic data for Chesapeake Bay spawning stocks resulted in the declaration of unknown stock status in a 2012 stock assessment and made it difficult to evaluate responses to conservation and restoration efforts. The objectives of the present study were to (1) conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(45 citation statements)
references
References 34 publications
4
41
0
Order By: Relevance
“…Although automatic analysis techniques have improved, manual processing is still the usual method to count and measure fish with DIDSON cameras within the scope of fish monitoring scientific surveys (Becker et al ., ; Crossman et al ., ; Doehring et al ., ; Lilja et al ., ; Ogburn et al ., ; Viehman & Zydlewski, ), but also in uses by different kinds of operators (for instance fish farmers, stakeholders, consultants, operators of once‐off surveys, etc .). Burwen et al .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although automatic analysis techniques have improved, manual processing is still the usual method to count and measure fish with DIDSON cameras within the scope of fish monitoring scientific surveys (Becker et al ., ; Crossman et al ., ; Doehring et al ., ; Lilja et al ., ; Ogburn et al ., ; Viehman & Zydlewski, ), but also in uses by different kinds of operators (for instance fish farmers, stakeholders, consultants, operators of once‐off surveys, etc .). Burwen et al .…”
Section: Introductionmentioning
confidence: 99%
“…Although automatic analysis techniques have improved, manual processing is still the usual method to count and measure fish with DIDSON cameras within the scope of fish monitoring scientific surveys (Becker et al, 2016;Crossman et al, 2011;Doehring et al, 2011;Lilja et al, 2010;Ogburn et al, 2017;Viehman & Zydlewski, 2015), but also in uses by different kinds of operators (for instance fish farmers, stakeholders, consultants, operators of once-off surveys, etc.). Burwen et al (2007Burwen et al ( , 2010 found a strong linear relationship (r 2 = 0.9) between manual DIDSON-based lengths and true lengths for a variable number of swimming fish at different ranges (i.e., distance to the camera).…”
Section: Introductionmentioning
confidence: 99%
“…One reason for the lack of response may be the bycatch in offshore fisheries, which was estimated at 727,400 Alewives and 1,069,000 Blueback Herring for the southern New England Atlantic Herring fishery during 2012-2013 (Hasselman et al 2016). This level of bycatch is substantial compared to the 2014 spawning run counts of 581,275 ± 31,970 Alewives and 726,450 ± 39,995 Blueback Herring in the largest documented Chesapeake Bay spawning run (Ogburn et al 2017) and other estimated run sizes in the region (ASMFC 2012). There may also have been insufficient time for the population to recover, or juvenile abundance indices may be relatively insensitive to changes in adult populations.…”
Section: Discussionmentioning
confidence: 88%
“…These differences in run timing MANAGEMENT BRIEF are consistent with spawning run counts in which both Alewives and Blueback Herring tend to arrive 1-3 weeks earlier in eastern shore tributaries (Choptank and Nanticoke rivers) than in upper western shore tributaries (Patapsco and Susquehanna rivers; M.B.O, unpublished data). Stream temperature is one important driver of spawning run timing for river herring (Ellis and Vokoun 2009;Ogburn et al 2017), but other mechanisms potentially driving observed differences in run timing are poorly understood. Temporal shifts in the genetic composition of river herring spawning runs in Chesapeake Bay tributaries warrant further attention and will require weekly sampling in more rivers and multiple years to determine whether it is a common phenomenon potentially explaining observed patterns of genic and genetic differentiation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation